CLIFF-GRADS Science Collaboration Series 2020 - Thematic student session: Rice systems - Sander, Björn Ole; Gebremedhin, Tegegnework; P, Sruthi; Idris, Sani; Mboyerwa, Primitiva; Cuong, Ong Quoc; Kashyap, Durba; Edwards, Glory (Global Research Alliance on Agricultural Greenhouse Gases (GRA) & CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS), 2020)
Learn more about the CLIFF-GRADS Program and Alumni: https://ccafs.cgiar.org/CLIFF-GRADS